Studi Komparasi Strategi Card Sort Dengan True Or False Terhadap Hasil Belajar Pendidikan Agama Islam Siswa Kelas Viii SMP N 3 Sawit Boyolali Tahun 2015/2016 - Lestari, Mutiah Yuni, Dr. Abdullah Aly, M.Ag (2017)
The success of an educational process is determined by the teacher, the students and the school environment. Although the teacher has explained about a material, but uncertainly the student can receive well. Therefore, teachers must innovate to provide learning fun, not boring and easily accepted by the students. One of them is the use of learning strategies is an effective way of presenting the material to the students that will have an effect on learning outcomes. In using these learning strategies students can know, understand and apply the information in the day life. The Activeness of students and student learning outcomes can be realized through the use of various learning strategies. Learning strategies that will lead students on learning objectives to be achieved. This study examines about: Is there a significant difference in the use of Card Sort strategy by True or False to the Islamic Religious Education Learning Outcomes Student grade VIII SMP N 3 Sawit, Boyolali 2015/2016 academic year. This research is experimental research with experimental designs Quasi-Experimental Designs types, that is design by providing test after both experimental groups were treated. The population in this study were all students of grade VIII SMP N 3 SAWIT BOYOLALI totaling 186 are divided into 6 classes. The sample used in this study is a sample of which the first experiment class VIII E totalled 31 students, the second experiment Class VIII G totaled 31 students. The sampling is random sampling. This data collection techniques using the test methods and documentation. While technical analysis with the study hypothesis test using t test data analysis. The results of this study concluded: (1) There are significant differences of Islamic Religious Education Learning Outcomes Student Grade VIII SMP N 3 SAWIT BOYOLALI 2015/2016 academic year with the Learning Strategy Card Sort by True or False in bad attitudes material that is reverenge and hypocritical (2) the score of Islamic Religious Education Learning Outcomes Student grade VIII SMP N 3 sawit BOYOLALI 2015/2016 academic year with the Learning Strategy Card Sort is higher than the use of Learning Strategies True or False. The average score of learning with the Card Sort strategy is 85.26, while the is True or False, 79.48.